Outcome of mentalization‐based and supportive psychotherapy in patients with borderline personality disorder: a randomized trial. (17th August 2012) - Jørgensen, C. R.; Freund, C.; Bøye, R.; Jordet, H.; Andersen, D.; Kjølbye, M.
<x xml:space="preserve">Abstract</x> Objective: This study presents data from a randomized outcome study comparing mentalization‐based and supportive psychotherapy for patients with borderline personality disorder (BPD). Method: Eighty‐five SCID‐II diagnosed borderline patients were randomized to either i) 2 years of intensive (twice weekly) combined (individual and group), mentalization‐based psychotherapy (MBT) or ii) 2 years of less‐intensive (biweekly) supportive group therapy. Treatment outcome was assessed using a battery of self‐report questionnaires, SCID‐II interviews and therapist‐rated global assessment of functioning (GAF). Results: Fifty‐eight patients completed 2 years of treatment. Significant changes in both treatment groups were identified for several outcome measures, including self‐reported measures of general functioning, depression, social functioning and number of diagnostic criteria met for BPD, as outlined by the SCID‐II interview. General linear modelling was used to compare treatment outcome in the two groups. Only GAF showed a significantly higher outcome in the MBT group. A trend was found for a higher rate of recovery from BPD in the MBT group. Pre‐post effect sizes were high (0.5–2.1) and for the most part highly significant in both groups. Conclusion: The study indicates that both MBT and supportive treatment are highly effective in treating BPD when conducted by a well‐trained and experienced psychodynamic staff in a well‐organized clinic.